Influence of adding several levels of dried parsley (Petroselinum crispum) on growth performance of broiler chicks - Saeed, Rozhgar (Sulaimani Journal for Pure and Applied Sciences, 2025)
The present research examines the impact of varying concentrations of dried parsley (Petroselinum crispum) supplementation on the growth performance, feed conversion ratio, and intestinal histological change of broiler chicks (Ross 308). A total of 224 one-day-old chicks (each group had equal replication) were randomly allocated to four distinct dietary treatments: T1 (control, standard diet), T2 (standard diet supplemented with 100g/kg of parsley), T3 (standard diet supplemented with 200g/kg of parsley), and T4 (standard diet supplemented with 300g/kg of parsley). Growth rate, feed intake, feed conversion ratio, and economic viability were ascertained. Results indicate significant increases in body weight gain, particularly in the early growth phases, with the highest gain being in the T2 and T4 groups. Parsley supplementation reduced feed consumption but concurrently improved feed efficiency, especially in T2. Higher levels of supplementation (T3, T4) had variable effects in enhancing some parameters but reducing intake efficiency in later stages. Intestinal morphology examination showed that mucosal thickness, villi height, and villi thickness were significantly increased in supplemented groups, indicating better nutrient absorption capacity. Economic analysis indicated that moderate inclusion of parsley (T2) was the most cost-effective. These results indicate that parsley in the diet (300-400g) can improve broiler performance, gut health, and economic returns and can be used as a natural substitute for synthetic feed additives.
Keywords: Broiler chicks; Feed additives; Parsley plant; development efficacy; Growth